Interferon Regulatory Factor 6 Is Necessary for Salivary Glands and Pancreas Development. (February 2018) - Metwalli, K.A.; Do, M.A.; Nguyen, K.; Mallick, S.; Kin, K.; Farokhnia, N.; Jun, G.; Fakhouri, W.D.
Interferon regulatory factor 6 ( IRF6 ) acts as a tumor suppressor and controls cell differentiation in ectodermal and craniofacial tissues by regulating expression of target genes. Haploinsufficiency of IRF6 causes Van der Woude and popliteal pterygium syndrome, 2 syndromic forms of cleft lip and palate. Around 85% of patients with Van der Woude express pits on the lower lip that continuously or intermittently drain saliva, and patients with the common cleft lip and palate have a higher prevalence of dental caries and gingivitis. This study aims to identify the role of IRF6 in development of exocrine glands, specifically the major salivary glands. Our transgenic mouse model that expresses LacZ reporter under the control of the human IRF6 enhancer element showed high expression of IRF6 in major and minor salivary glands and ducts. Immunostaining data also confirmed the endogenous expression of IRF6 in the developing ductal, serous, and mucous acinar cells of salivary glands. As such, we hypothesized that Irf6 is important for proper development of salivary glands and potentially other exocrine glands. Loss of Irf6 in mice causes an increase in the proliferation level of salivary cells, disorganized branching morphogenesis, and a lack of differentiated mucous acinar cells in submandibular and sublingual glands. Expression and localization of the acinar differentiation marker MIST1 were altered in Irf6 -null salivary gland and pancreas. The RNA-Seq analysis demonstrated that 168 genes are differentially expressed and confer functions associated with transmembrane transporter activity, spliceosome, and transcriptional regulation. Furthermore, expression of genes involved in the EGF pathway—that is, Ereg, Ltbp4, Matn1, Matn3, and Tpo —was decreased at embryonic day 14.5, while levels of apoptotic proteins were elevated at postnatal day 0. In conclusion, our data report a novel role of Irf6 in exocrine gland development and support a rationale for performing exocrine functional tests for patients with IRF6 -damaging mutations.